2010
DOI: 10.3758/pbr.17.4.550
|View full text |Cite
|
Sign up to set email alerts
|

Viewing-position effects in the Stroop task: Initial fixation position modulates Stroop effects in fully colored words

Abstract: 550In the Stroop task (Stroop, 1935), participants are instructed to name the color of the ink in which stimuli are presented. A Stroop experiment classically compares three conditions. In the incongruent condition, the stimulus is a color word that is printed in a different color from the one it designates (e.g., the word BLUE printed in green). In the congruent condition, the word and the ink color correspond. Finally, the control condition consists of neutral words or nonwords and provides a baseline for as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The optimal viewing position effect. It is important to note that, with the Stroop effect, the interference created by a mismatch between the word name and the ink color is strongest when people are looking at the center of the word than when they are fixating more peripheral letters (Perret & Ducrot, 2010). This is important because of another robustly demonstrated effect-the optimal viewing position (OVP) effect-in which words that are presented in isolation are recognized more efficiently when people are looking in the center of the word than when they are looking at more external letters (O'Regan, Lévy-Schoen, Pynte, & Brugaillère, 1984).…”
Section: Word Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…The optimal viewing position effect. It is important to note that, with the Stroop effect, the interference created by a mismatch between the word name and the ink color is strongest when people are looking at the center of the word than when they are fixating more peripheral letters (Perret & Ducrot, 2010). This is important because of another robustly demonstrated effect-the optimal viewing position (OVP) effect-in which words that are presented in isolation are recognized more efficiently when people are looking in the center of the word than when they are looking at more external letters (O'Regan, Lévy-Schoen, Pynte, & Brugaillère, 1984).…”
Section: Word Recognitionmentioning
confidence: 99%
“…The pair of panels at the bottom show the participant's potential responses. letters (Perret & Ducrot, 2010). This is important because of another robustly demonstrated effect-the optimal viewing position (OVP) effect-in which words that are presented in isolation are recognized more efficiently when people are looking in the center of the word than when they are looking at more external letters (O'Regan, Lévy-Schoen, Pynte, & Brugaillère, 1984).…”
Section: Word Recognitionmentioning
confidence: 99%
“…This study found that adults with ADHD fixated longer and more times on the target than the distractor and that these adults made more transitions between the two than adults without ADHD. Interestingly, both interference and facilitation (Stroop effects) are reduced when the first fixation is controlled and the first fixation is located at the end of the word instead of the optimal viewing position (Perret & Ducrot, 2010).…”
Section: The Stroop Test and Congruent And Incongruent Coloursmentioning
confidence: 99%